Red jacket : a Lute Bapcat mystery - Heywood, Joseph (Heywood, Joseph. Lute Bapcat mystery., 2012)
Meet Lute Bapcat, orphan, loner, former cowboy, Rough Rider, beaver trapper, a man who in 1913, with the enthusiastic recommendation by Theodore Roosevelt, himself, becomes one of the Michigan's first civil service game wardens. His territory: The Keweenaw Peninsula, the state's industrial center. Featuring a stunning array of characters, fascinating historical detail, and Heywood's trademark writing about life and work in Michigan's wild, Red Jacket asks Lute to confront an explosive, bloody labor strike; a siege-like sabotage, including a sudden rash of decapitated, spoiled deer; poisoned trout streams and well water; and unusual deforestation - all apparently designed by mine owners to deny nature's bounty to the strikers, and thereby to break the union. The strike's violence culminates in the Italian Hall disaster, during which a man allegedly yells fire in a small building with several hundred people inside. In the panic, 73 people are crushed or die of suffocation, the majority of them the children and wives of striking miners at the hall for a Christmas party. Even with good people dying, the Michigan governor refuses to take sides. Should Lute Bapcat?